Secondary metabolites produced by marine actinomycete Micromonospora sp. A258. Issue 6 (8th January 2020) - Van Nam, Vu; Huong, Doan Thi Mai; Dao, Phi Thi; Anh, Nguyen Mai; Minh, Le Thi Hong; Van Cuong, Pham
Abstract: In the course of our screening program, the EtOAc extract of Micromonospora sp. A258 from the sponge Haliclona oculata exhibited antimicrobial activity against both gram positive S.aureus ATCC25923 and gram‐negative E.coli ATCC25922, S.enterica ATCC13076. This paper reports the isolation and structural elucidation of eight secondary metabolites including bacilsubteramide A (1 ), 4, 9‐dihydroxy‐3‐isobutyl‐2, 3, 4, 5‐tetrahydrobenzo‐azepin‐1‐one (2 ), indole‐3‐carboxylic acid (3 ), N ‐acetyltryptamine (4 ), N ‐(4‐hydroxyphenyl)ethyl‐methylbutanamide) (5 ), N ‐phenyl‐acetamide (6 ), 2‐[(5‐methyl‐1, 4‐dioxan‐2‐yl)methoxy]ethanol (7 ), (2 R, 3 S )‐butane‐2, 3‐diol (8 ) from the culture broth of Micromonospora sp. A258. Their structures were determined by spectroscopic analysis including MS, 1D NMR and 2D NMR, as well as comparison with literature data.